Czech Republic: health system review - Alexa, Jan; Recka, Lukas; Votapkova, Jana; van Ginneken, Ewout; Spranger, Anne; Wittenbecher, Friedrich (Health systems in transition, 2015)
This analysis of the Czech health system reviews recent developments in organization and governance, health financing, health-care provision, health reforms and health system performance. The Czech health-care system is based on compulsory statutory health insurance providing virtually universal coverage and a broad range of benefits, and doing so at 7.7 % of GDP in 2012 - well below the EU average - of which a comparatively high 85 % was publicly funded. Some important health indicators are better than the EU averages (such as mortality due to respiratory disease) or even among the best in the world (in terms of infant mortality, for example). On the other hand, mortality rates for diseases of the circulatory system and malignant neoplasms are well above the EU average, as are a range of health-care utilization rates, such as outpatient contacts and average length of stay in acute care hospitals. In short, there is substantial potential in the Czech Republic for efficiency gains and to improve health outcomes. Furthermore, the need for reform in order to financially sustain the system became evident again after the global financial crisis, but there is as yet no consensus about how to achieve this.
Keywords: dospělí; vládní programy; všeobecné zdravotní pojištění; zdravotní politika; Female; Infant; dítě; předškolní dítě; novorozenec; financování zdravotní péče; Adult; ženské pohlaví; mladý dospělý; Health Care Reform; Universal Health Insurance; Adolescent; Healthcare Financing; lékařská podpora; lidé; Infant, Newborn; Government Programs; poskytování zdravotní péče; Delivery of Health Care; Health Policy; výdaje na zdravotnictví; Male; zdravotnické zdroje; kojenec; Aged; Czech Republic; Health Resources; Child, Preschool; reforma zdravotní péče; Young Adult; Česká republika; lidé středního věku; Child; senioři; mužské pohlaví; Medical Assistance; Middle Aged; mladiství; Health Expenditures; Humans